The Instrumental Role of Social Media as A Functional Means in The Development of Character Education - Everhard Markiano Solissa; Al Ghazali Al Ghazali; Reviandari Widyatiningtyas; Elly Retnaningrum; Jolanda Dessye Parinussa (Jurnal Pendidikan dan Konseling (JPDK), 2023)
This research aims to determine the instrumental role of social media as a functional means of developing character education. The method used in this research was qualitative. Data collection techniques used in this research were literature studies and documentation. The data collected was then analyzed descriptively qualitatively. The results of this research indicated that the instrumental role of social media is a functional means of developing character education, which plays a role in shaping the character of students who are skilled in understanding information. In the context of character education, the ability to understand information is to shape the character of students who think critically. Another role of social media in the development of character education is to form honest, open, transparent and courageous characters. Character education learning that is built is to teach students to dare to convey the truth of an event through social media. Another role of social media is to shape the character of tolerance. To teach a tolerant character to students, the teacher can do this by inviting them to look for and watch social media that contains tolerance. The development of character education with social media can be done by asking students to spread tolerance through words through their respective accounts.